2014
DOI: 10.1136/bjophthalmol-2014-305510
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in primary powered endoscopic dacryocystorhinostomy

Abstract: Powered endoscopic DCR is a safe procedure and offers excellent long-term results. Adjunctive endonasal procedures should be performed where indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 20 publications
4
42
0
Order By: Relevance
“…17 However stents themselves have their own set of Mohammad Javed Ali: I perform Powered Endoscopic DCR with a 360 0 mucosa to mucosa approximation, a technique which I believe is the most physiological among the existing approaches. 20,21 The success of this approach in the hands of trainees and less experienced surgeons is also encouraging.…”
Section: Ruchi Goelmentioning
confidence: 87%
“…17 However stents themselves have their own set of Mohammad Javed Ali: I perform Powered Endoscopic DCR with a 360 0 mucosa to mucosa approximation, a technique which I believe is the most physiological among the existing approaches. 20,21 The success of this approach in the hands of trainees and less experienced surgeons is also encouraging.…”
Section: Ruchi Goelmentioning
confidence: 87%
“…Patients were chosen alternatively into each group; odd-numbered patients were assigned to the mechanical burr group and even-numbered patients were assigned to the piezoelectric or ultrasonic group. The surgery was performed as per standard protocols as described, [1][2][3][4] and all patients were operated on by a single surgeon (M.J.A. ), who was equally experienced with both the instruments.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] The key steps for a successful outcome are creation of an ostium large enough to completely expose the entire length of the lacrimal sac, full-length sac marsupialization, and complete mucosa to mucosa approximation to encourage healing by primary intention. [1][2][3][4] Superior osteotomy is an important step to achieve full exposure of the sac, and various modalities have been employed to achieve this, including use of chisel and mallet, special bone nibblers, lasers, mechanical burrs, and ultrasonic emulsification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported success rates as low as 57%, while others have reported success rates of 100%. [4][5][6] A recent retrospective review of 1083 END-DCRs performed by a single surgeon reported a success rate of 92.7%. 7 The reasons for this variation are unclear but probably include differences in patient selection, exact surgical approach, surgeon experience, time to follow-up, and definition of 'success'.…”
Section: Introductionmentioning
confidence: 99%